Strain-compensated GaAs1−yPy/GaAs1−zBiz/GaAs1−yPy quantum wells for laser applications. (September 2015) - Kim, H; Forghani, K; Guan, Y; Luo, G; Anand, A; Morgan, D; Kuech, T F; Mawst, L J; Lingley, Z R; Foran, B J; Sin, Y
Abstract GaAs1−zBiz/GaAs1−yPy strained-compensated quantum well (QW) structures for laser applications were grown by metalorganic vapor phase epitaxy. The band offsets for the GaAs1−zBiz/GaAs1−yPy heterojunction were calculated by the density functional theory, and the design of strain-compensated structures was undertaken by the zero stress analysis. The post-growth thermal annealing of the structures dramatically increases the photoluminescence intensity compared to that from as-grown GaAs1−zBiz QW samples. Transmission electron microscopy studies verified layer thicknesses as well as the presence of abrupt interfaces in the annealed GaAs1−zBiz/GaAs1−yPy QW structure. Electroluminescence measurements from ridge-waveguide devices show broad spectral emission characteristics and lasing was not observed up to a current injection of 4 kA cm−2.